2014
DOI: 10.3390/rs6098779
|View full text |Cite
|
Sign up to set email alerts
|

Can I Trust My One-Class Classification?

Abstract: Contrary to binary and multi-class classifiers, the purpose of a one-class classifier for remote sensing applications is to map only one specific land use/land cover class of interest. Training these classifiers exclusively requires reference data for the class of interest, while training data for other classes is not required. Thus, the acquisition of reference data can be significantly reduced. However, one-class classification is fraught with uncertainty and full automatization is difficult, due to the limi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(40 citation statements)
references
References 55 publications
2
38
0
Order By: Relevance
“…This phenomenon might have resulted from the different thresholds that were used to transform the model outputs into binary classes. Studies have found that the default threshold performed relatively poorly as compared with a threshold obtained from alternative threshold selection strategies, and might be insufficient to balance false positive and false negative classifications [17,57]. Although threshold selection strategies can improve the classification results, the addition of such a procedure has the disadvantage of increasing the complexity of model selection.…”
Section: Discussionmentioning
confidence: 99%
“…This phenomenon might have resulted from the different thresholds that were used to transform the model outputs into binary classes. Studies have found that the default threshold performed relatively poorly as compared with a threshold obtained from alternative threshold selection strategies, and might be insufficient to balance false positive and false negative classifications [17,57]. Although threshold selection strategies can improve the classification results, the addition of such a procedure has the disadvantage of increasing the complexity of model selection.…”
Section: Discussionmentioning
confidence: 99%
“…As a general-purpose machine learning method, the Maximum entropy (Maxent) approach [56,57,75] is also suitable for mapping real distributions based on remote sensing data [29,36,45,[51][52][53]55,[58][59][60]62]. Maxent is available free for educational and noncommercial use as a multi-platform Java-based software [76]).…”
Section: Maxent Model and Tuning Of Complexitymentioning
confidence: 99%
“…Third, a semi-supervised method: BSVM. These two methods (BSVM and OCSVM) were selected because they have been previously used in a variety of studies with remotely-sensed data, such as [13,17,19,37,40].…”
Section: Introductionmentioning
confidence: 99%